Prarancangan Pabrik Etilen Glikol Dari Etilen Oksida Dengan Proses Dow Meteor - Irma Damayanti; Sunarno Sunarno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Ethylene glycol is a hygroscopic liquid with low volatility. Ethylene glycol is colorless, odorless, has a low viscosity. Ethylene glycol is used as a polyester resin for fibers, a film-making agent, an antifreeze and coolant agent, a heat exchange agent, a waterbased formula, and an unsaturated polyester. The purpose of establishing an ethylene glycol factory is expected to be able to support efforts to save the country's foreign exchange through import substitution of ethylene glycol, and increase employment. Ethylene glycol factory with a capacity of 200,000 tons / year in Batam, Riau Islands. The ethylene glycol production process is carried out through the Dow METEOR process which consists of 4 stages, namely the standard discussion stage, the ethylene glycol formation stage, the ethylene glycol concentration stage, and the product separation stage. The main design is the CSTR reactor, which is used to react ethylene oxide with water to form ethylene glycol with the by-products of diethylene glycol and triethylene glycol. Based on the results of the economic feasibility analysis of the factory, the ethylene glycol plant is feasible to establish with a Payback Period (PBB) obtained of 2 years, an IRR of 22.738%, a Percent Return on Investment (ROI) is 30.59%, and a Break Event Point (BEP) is obtained by 60%. Keywords: Ethylene glycol, dow meteor, cstr reactor